Assume that "\\displaystyle\\sum_{n=0}^\\infin a_nx^n" is a solution. Then you have
"\\displaystyle\\sum_{n=2}^\\infin n(n-1)a_nx^{n-2}=\\displaystyle\\sum_{n=0}^\\infin a_nx^{n}"
"\\displaystyle\\sum_{n=0}^\\infin(n+2)(n+1)a_{n+2}x^{n}=\\displaystyle\\sum_{n=0}^\\infin a_nx^{n}"
By equating coefficients, we have
We obtain the recursion formula
"a_0, a_1"
"a_{2}=\\dfrac{a_0}{1\\cdot2} , \\ \\ \\ \\ \\ a_{3}=\\dfrac{a_1}{2\\cdot3}"
"\\vdots\\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\vdots"
"a_{2k}=\\dfrac{a_0}{(2k)!} , \\ \\ \\ \\ \\ a_{2k+1}=\\dfrac{a_1}{(2k+1)!}"
Thus, we can represent the general solution as the sum of two series—one for the
even-powered terms with coefficients in terms of "a_0" and one for the odd-powered
terms with coefficients in terms of "a_1"
The solution has two arbitrary constants, and as we would expect in the
general solution of a second-order differential equation.
Comments
Leave a comment